Application of Copy Number Variation Detection to Fetal Diagnosis of Echogenic Intracardiac Focus During Pregnancy - Song, Yaxian; Xu, Jingjing; Li, Hongmiao; Gao, Jiong; Wu, Limin; He, Guoping; Liu, Wen; Hu, Yue; Peng, Yaqin; Yang, Fang; Jiang, Xiaohua; Wang, Jing (Frontiers in Genetics, 2021)
Echogenic intracardiac focus (EIF) is one of the most common ultrasound soft markers in prenatal screening. However, the association of EIF with chromosomal abnormalities is still controversial. From January 2018 to April 2020, a total of 571 fetuses with ultrasound soft markers (USMs) in our center were enrolled, among which 150 (26.27%) presented EIFs. We analyzed the karyotype anomalies and copy number variations (CNVs) in fetuses who presented EIFs by comparing their ultrasound indications, maternal ages and gestational stages. There were no statistically significant differences in the incidence of chromosomal abnormalities between fetuses with EIFs and the fetuses with USMs (4.00% vs. 7.71%, p=0.112). Additionally, the incidence of chromosomal abnormalities was not related to maternal age (4.10% in maternal age below 35 yeas vs. 3.57% in maternal age above 35, p=1.000). Interestingly, after 28 weeks of gestation, fetuses with EIFs showed more chromosomal abnormalities (20.00%) than that in the group before 28 weeks of gestation (2.22%, p=0.014), and this result was attributed to the detection of pathogenic CNVs. After birth, 25 of children conducted cardiac development re-examination. Among them, 9 (36%, 9/25) were diagnosed with congenital heart disease, primarily patent foramen oval and ventricular septal defects (7/9, 77.77%). We concluded that the appearance of EIFs in early or mid-trimester would not indicate an increased risk of fetal chromosomal abnormalities. However, the persistence of EIFs in late trimester was associated with a higher risk of pathology-related CNVs and its persistent appearance may indicate heart development defects after birth. Thus, our results suggest that CNV detection has its advantages in prenatal diagnosis, especially for those with EIFs that persist in the third trimester.